Common defects on pre-war school / Eirina Abdul Hadi - Abdul Hadi, Eirina (Faculty of Architecture, Planning and Surveying, 2010)
In Malaysia, the dilapidation surveys are gaining momentum and are often required by the building owners or clients. Dilapidation surveys are usually prepared in anticipation of the work required to rectify any identified building defect, hence, they are best conducted as part and parcel of the documentation for these works. The lack of maintenance on the building can causing the building has many problems according the structure, services and fabric of the affected building. The defect is maybe caused of the age of the building where the causes of defect such as wear and tear, applied forces, gases or liquids, biological agents and climate or temperature will occurred along age of the building. The objective of the study common defect on the Heritage School is to identify the common defect on the pre-war school, to determining the causes of the building defects, to give recommendation on upgrading the current maintenance of pre-war school.